Activity of Trichoderma asperellum Strain ICC 012 and Trichoderma gamsii Strain ICC 080 Toward Diseases of Esca Complex and Associated Pathogens - Di Marco, Stefano; Metruccio, Elisa Giorgia; Moretti, Samuele; Nocentini, Marco; Carella, Giuseppe; Pacetti, Andrea; Battiston, Enrico; Osti, Fabio; Mugnai, Laura (Frontiers in Microbiology, 2022)
Grapevine trunk diseases are widespread in all grape growing countries. The diseases included in the Esca complex of diseases are particularly common in European vineyards where their distinctive foliar symptoms are well known to be associated with losses in quantity and quality of the crop. Protection of pruning wounds is known to reduce infections in artificial inoculations and to some extent reduce the external leaf symptoms. The application of biological control agents in the field is typically started at the first appearance of symptoms. In this paper the two strains belonging to two different species Trichoderma asperellum ICC 012 and T. gamsii ICC 080, which are present in a commercial formulation, were tested in vitro, in vivo in artificial inoculation and in the field in long term experiments where the wounds on four young asymptomatic vineyards were protected since one or two year after planting. The in vitro trials highlighted the different temperature requirements of the two strains, the direct mycoparasitizing activity of T. asperellum and the indirect activity shown by both Trichoderma strains. In vivo trials confirmed the ability of the two strains to reduce the colonization following artificial inoculations with the high, unnatural concentration of spores used in artificial infections, even if with variable efficacy, and with a long persistence as they could be reisolated after 7 months from treatment. The preventive applications carried out over 9 years showed a very high reduction in symptom development in the treated vines, on annual and cumulated incidence and on death of the vines, with a disease reduction varying from 66% to almost 90%. Early and annual application of the protection to pruning wounds appears to be the best method for reducing damages caused by Grapevine Leaf Stripe Disease (a disease of the Esca complex of diseases) and Trichoderma, in the presence of a natural inoculum concentration, appears to offer an efficient, environmentally friendly and long-lasting protection.